Global research trends in catheter ablation and surgical treatment of atrial fibrillation: A bibliometric analysis and science mapping - Gao, Xiang; Liu, Kai; Zhao, Xinke; Lv, Xinfang; Wu, Xue; Ren, Chunzhen; Chen, Qilin; Li, Yingdong (Frontiers in Surgery, 2023)
Introduction: To evaluate the global research results of the catheter ablation and surgical treatment of atrial fibrillation in the past 40 years by bibliometrics, and to explore the hotspots and prospects for future development. Methods: Relevant literatures were selected from the Web of Science Core Collection. VOSviewer 1.6.17, SciMAT 1.1.04, and CiteSpace 5.8.R1 were used to analyze the data objectively, deeply and comprehensively. Results: As of July 14, 2021, 11,437 studies for the catheter ablation and surgical treatment of atrial fibrillation have been identified from 1980 to 2021. The Journal of Cardiovascular Electrophysiology and Circulation respectively ranked first in terms of the number of publications and the number of co-citations. A total of 6,631 institutions from 90 countries participated in the study, with USA leading the way with 3,789 documents. Cryoablation, atrial fibrosis, substrate modification, minimally invasive and access surgery will still be the research focus and frontier in the next few years. Conclusions: The publication information for the catheter ablation and surgical treatment of atrial fibrillation were reviewed, including country, institution, author, journal publications, and so on. Developed countries had the advantage in this research areas, and cooperation with low-income countries should be improved. The former research hotspots in the field of catheter ablation and surgical treatment of atrial fibrillation were analyzed, and the future research direction was predicted.